The Effect of Service Quality on Customer Satisfaction at AirAsia Indonesia - Dilla Pratiyudha; Amaliya Amaliya (Journal Hotspot, 2021)
Airlines compete with each other to provide the best service in order to increase the number of customers. One of the domestic airlines including Low Cost Carrier is AirAsia Indonesia which is based in Tangerang, Banten, and serves domestic and foreign flight routes. The purpose of this study is to determine the effect of AirAsia Indonesia staffs’ service quality towards the customer satisfaction. This research uses quantitative descriptive methods. Primary data of this study were collected by distributing questionnaires to 100 respondents who use the airline. Data analysis uses validity test, reliability test, descriptive statistics, correlation test, coefficient of determination, and simple linear regression test. It is found that R Count> R Table so all statements in the questionnaire distributed to respondents were valid. From the results of data processing, it can be seen that the quality of service has a fairly high influence on customer satisfaction at AirAsia Indonesia, as much as 65.9%.